Supporting formative assessment in content and language integrated learning: the MWS-Web platform. (2014) - Taibi, Davide; Kantz, Deirdre; Fulantelli, Giovanni
Integrating specific technology-enhanced learning activities in a traditional curriculum is an important challenge in CLIL (Content and Language Integrated Learning) scenarios. As a matter of fact, monitoring student learning by means of formative assessment practices is successfully used to supervise learning progress and to recognise students' efforts in university learning environments, including CLIL courses. Preliminary results of a pilot experimentation of the MWS-Web platform specifically designed to support both learners' activities and their assessment conducted within the degree course in Dentistry at the University of Pavia are presented. The MSW-Web Storyboard was used by the teachers for formative assessment practices. A backwards stepwise regression model was developed in order to establish the relationship between the students' interactions in the MWS-Web platform and their learning performance. In particular, the model has provided significant clues that lead to consider the students' interactions on the MWS-Web Storyboard as an important factor to support formative assessment practices.